Editorial - Editor, (Dev Sanskriti Interdisciplinary International Journal, 2018)
Born out of a unique vision of the groundbreaking scholar and great visionary, Pandit Shri Ram Sharma Acharya, Dev Sanskriti Vishwavidyalaya is an educational institution to mould its students into noble and enlightened human beings; selfless, warm hearted compassionate and kind individuals. Along with excellent domain focused approach, categorical excellence and a widely knitted outreach connect, the University aims to build individuals with spirituality as their locus of control and help to excel holistically through meticulously designed curriculum and dedicated faculty. One of the primary objectives of the University is to provide education and conduct research in the disciplines of Vedic Culture (Dev Sanskriti) and to provide a proper blend of science and spirituality. This issue of Dev Sanskriti: Interdisciplinary International Journal is a welcome addition in the same tradition. In the present time, alternative and sustainable sources in entrepreneurship are needed. Indian rural entrepreneurship sector has a huge scope to contribute financial and economical aspects of India. Ancient Indian economy rotated around cow-based products. This model is being revived in many parts of India including Dev Sanskriti Vishwavidyalaya. The paper by KS Tyagi, DP Singh, TC Sharma, RK Gupta presented a rural entrepreneurship model based on cow based products. The second paper is dedicated to importance of nature; Dipankar Kumar evaluated the effect of Green and Non-Green Environment on Mental Health and Emotional Maturity. In his research he found that green environment highly impacts our overall dimensions of life i.e. physical, mental, emotional as well as spiritual health. The next paper Ipsit Pratap Singh studied the Vedic System of Management and explored the concept of Vedic Management with thrust on modern management principles in combination with the Vedic wisdom of life regulation. Pallavi, et. Al investigated the importance of key techniques to increase healthy life style through health tourism with especial reference to Ashtang yoga. In next paper Purva G. Sharma and Gopal Krishna Sharma did the review study and proposes yoga as a complementary therapy to mind-body alternative medicine intervention to improve physical and mental health conditions in children. We hope this mix of interdisciplinary flavor will certainly bring home a lot of learning to all our readers and subscribers. Stay connected for more in the subsequent volumes. Finally we heartily congratulate and thank the reviewers and all the contributors. We also hope that this issue of Journal will inspire and generate interest among researchers, educators, policymakers and professionals to understand the significance of Indigenous knowledge in present era. We also thank all the readers and seekers for their valuable feedback to make the journal a more effective vehicle in the field of Indigenous knowledge.